Radio resource management: The vital subject for evolution to 5G - Ali, Ayesha Haider; Nazir, Mohsin (ISWSN : 2017 International Symposium on Wireless Systems and Networks : 19-22 November 2017, 2017)
In this article, we will discuss radio resource management (RRM) as one of the major techniques for 5G networks. RRM involves sharing of the scarce spectrum among all users of the system. It includes performance gains in terms of efficient energy usage, higher throughput, lower delays, and decreased packet loss. We can take full advantage from RRM by efficient design strategies, fair resource allocation and competent packet scheduling. The goal of this paper is to present a comprehensive overview along with algorithms for RRM techniques that majorly focus on 1) efficient power utilization, 2) delay reduction and 3) throughput maximization. In this paper we will discuss various potential techniques for efficient resource planning in terms of power, throughput and delay. Some findings are also discussed to illuminate the shift towards the next generation networks.